When is Austerity Ineffective? - Luigi Marattin (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2013)
This paper offers a formal analysis of the relationship between changes in government primary balance and debt-to-GDP ratio. it establishes the conditions under which a fiscal consolidation increases - instead of decreasing - the stock of government liabilities relative to aggregate output. A crucial role is played by the relationship between the elasticities of average cost of debt and nominal output to primary balance: while the former depends on debt maturity and risk premia dynamics, the latter relates to the well-known controversy on the size of government spending multipliers. The paper shows an application to the ongoing fiscal consolidation process in the Eurozone.
Keywords: E62; H32; 330